Faktor Kecemasan Siswa Dalam Berbicara Bahasa Inggris pada Mahasiswa Universitas Muhammadiyah Jakarta - Fadhilah, Izzatunnisa (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
English is the language of communication used all over the world, the ability to speak English is the main priority of many languages studied by students today. One of the factors that prevent students from speaking English is anxiety. This study aims to determine what anxiety factors are experienced by fifth semester students of Muhammadiyah University of Jakarta in the English learning environment based on their views. The method used in this research is qualitative with a descriptive approach. Based on the results of internal observations through Whatsapp chat media, as many as three students were selected as respondents who were briefly interviewed. Research data were collected through literacy and interviews, during the research the researchers read a lot and found out about things related to student anxiety. Theresults of this study indicate that the anxiety factors that cause students to be unable to speak English in class are shyness, less confidence, fear of making mistakes, grammatical problems and lack of vocabulary.